2011
DOI: 10.1261/rna.029777.111
|View full text |Cite
|
Sign up to set email alerts
|

A role for transcription from a piRNA cluster in de novo piRNA production

Abstract: PIWI-interacting RNAs (piRNAs) are at the heart of the nucleic acid-based adaptive immune system against transposons in animal gonads. To date, how the piRNA pathway senses an element as a substrate and how de novo piRNA production is initiated remain elusive. Here, by utilizing a GFP transgene, we screened and obtained clonal silkworm BmN4 cell lines producing massively amplified GFP-derived piRNAs capable of silencing GFP in trans. In multiple independent cell lines where GFP expression was silenced by the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
57
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 40 publications
4
57
0
Order By: Relevance
“…Indeed, such flexibility has been documented in recent studies. First, attempts to generate transgenic silkworm cell lines showed a remarkable incidence of transgenes integrating into piRNA clusters, supporting the idea that piRNA clusters act as a sink for active transposable elements (Kawaoka et al 2012). Furthermore, studies in mouse and Drosophila showed that inserting GFP sequences in piRNA clusters resulted in GFP-derived piRNAs and stable silencing of GFP in trans (Muerdter et al 2012).…”
Section: Introductionmentioning
confidence: 76%
“…Indeed, such flexibility has been documented in recent studies. First, attempts to generate transgenic silkworm cell lines showed a remarkable incidence of transgenes integrating into piRNA clusters, supporting the idea that piRNA clusters act as a sink for active transposable elements (Kawaoka et al 2012). Furthermore, studies in mouse and Drosophila showed that inserting GFP sequences in piRNA clusters resulted in GFP-derived piRNAs and stable silencing of GFP in trans (Muerdter et al 2012).…”
Section: Introductionmentioning
confidence: 76%
“…In the current model for piRNA-RISC formation, single-stranded primary transcripts are first produced from piRNA-generating loci. Then, these transcripts are likely fragmented into precursor piRNAs (pre-piRNAs) that are longer than mature piRNAs, through multiple steps including endonucleolytic cleavage by Zucchini (Brennecke et al 2007;Klattenhoff et al 2009;Ipsaro et al 2012;Kawaoka et al 2012;Muerdter et al 2012;Nishimasu et al 2012). A subset of PIWI proteins (e.g., Siwi in the silkworm) preferentially binds to pre-piRNAs with 5 ′ U (1U) (Brennecke et al 2007;Gunawardane et al 2007; Kawaoka et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…We know that piRNAs are longer in length than miRNAs and endo-siRNAs (at 25–31 nt), the 3' terminal 2' oxygen is methylated by the Hen1 enzyme, and there are many putative helicases, putative endonucleases, and tudor-domain containing proteins genetically required to generate and/or stabilize piRNAs (Ishizu et al 2012). However, our mechanistic picture of the functions for these Piwi pathway genes remains murky: the only in vitro piRNA biogenesis activity known is a “Trimmer” activity observed in Bombyx gonadal cell extracts which can trim a long 5' phosphorylated transcript bound by SIWI into a mature piRNA (Kawaoka et al 2012). And even though genetic advances that place artificial sequences like GFP into a piRNA precursor can give rise to artificial piRNAs (Kawaoka et al 2012; Muerdter et al 2012), we still cannot predict exactly which piRNAs would be generated most abundantly from these piRNA-generating transgenes.…”
Section: The Piwi Pathway: a Germ Cell Innovationmentioning
confidence: 99%
“…However, our mechanistic picture of the functions for these Piwi pathway genes remains murky: the only in vitro piRNA biogenesis activity known is a “Trimmer” activity observed in Bombyx gonadal cell extracts which can trim a long 5' phosphorylated transcript bound by SIWI into a mature piRNA (Kawaoka et al 2012). And even though genetic advances that place artificial sequences like GFP into a piRNA precursor can give rise to artificial piRNAs (Kawaoka et al 2012; Muerdter et al 2012), we still cannot predict exactly which piRNAs would be generated most abundantly from these piRNA-generating transgenes.…”
Section: The Piwi Pathway: a Germ Cell Innovationmentioning
confidence: 99%